PENGARUH PENGGUNAAN TEKNOLOGI PEMBELAJARAN BERBASIS LCD PROYEKTOR TERHADAP MINAT BELAJAR SISWA PELAJARAN SKI DI SMP AL-ISLAM 1 SURAKARTA - Afifah, Alimah Nur; Praptiningsih, Praptiningsih; Ulfah, Yetty Faridatul (STKIP Pesisir Selatan, 2026)
The Islamic Cultural History (SKI) subject in junior high schools is often perceived as boring and gains low student interest due to its emphasis on memorizing historical figures, dates, and events. Integrating LCD projector-based learning technology is expected to make learning more visually engaging and thereby increase students’ interest. This study aims to examine the influence of using LCD projector media on students’ learning interest in SKI at SMP Al-Islam 1 Surakarta in the 2025/2026 academic year. The research employed a quantitative correlational approach. A sample of 69 eighth-grade students was selected via proportional random sampling from a population of 222 students. Data were collected using questionnaires on the frequency and quality of teachers’ LCD projector usage (independent variable X) and on students’ interest in learning SKI (dependent variable Y). The results showed that the level of LCD projector usage was in the moderate category (on average 63.77% of the maximum score) and students’ learning interest was also moderate (63.77%). Pearson product-moment correlation testing yielded r = 0.976 with p = 0.000 (< 0.05), indicating a very strong and significant positive relationship between LCD projector use and students’ learning interest. The use of LCD media accounted for 95.2% of the variance in learning interest (R² = 0.952). In conclusion, the utilization of LCD projector-based learning technology has a positive and significant effect on enhancing students’ interest in learning SKI. Teachers are advised to further innovate in using LCD media with varied and active learning methods so that learning becomes increasingly engaging and participatory.